Human Resource Management Through Commercialised Professional Education in India: A Bane or A Boon - Sharma, Deepak; Singhal, R. K. (Journal of Commerce and Trade, 2017)
Career opportunities and rewards are very important factors in providing a development climate in educational institutions and agencies. If there is no developmental climate and no pressure or incentives for development, people are not likely to develop. The greatest HRM need in the education sector today is to change attitudes and systematic rigidities. This change should begin from the top. This change cannot come merely through training programs. The performance of the higher level officers should be assessed and feedback should be given to them on their innovativenes, initiative and activities geared to develop local level talent in the education system. This study is important because there is far too much to be done in the field of professional education to realize our dream. An organizational climate is required to be created in the field of education which should have profound influence on the outlook, well-being and attitudes of organizational members and thus, on their overall performance. It also provides a useful platform for understanding the characteristics of organization such us stability. creativity, motivation, and communication, etc. The traditional educational subjects are downgraded in the name of occupationally-sound degree options. In commercialized learning, higher educaiton degrees focus more on the job they fulfill and less on the traditional academics, such as sciences and liberal arts. This isn’t necessarily a bad thing for you, the online learner, if you’re going to school to acquire a degree for a new job opportunity.